2000
DOI: 10.1139/g00-012
|View full text |Cite
|
Sign up to set email alerts
|

Production of inbred progenies of diploid potatoes using anS-locus inhibitor (Sli) gene, and their characterization

Abstract: To develop inbred lines from self-incompatible, cultivated diploid potatoes, an S-locus inhibitor (Sli) gene derived from a self-compatible variant of a wild potato species, Solanum chacoense, was incorporated into various cultivated diploid potatoes. The progeny was selfed twice by the action of the Sli gene to obtain 74 S2 inbred clones belonging to 8 families. More than 40% of them were either non-flowering or pollen sterile. Among the pollen fertile clones, self-compatible clones occurred with a much lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…Recently, we found a dominant gene, named S-locus inhibitor gene (Sli), which is sporophytically expressed to inhibit a function of Sallele in pollen, and alters self-incompatible plants to self-compatible ones (Hosaka & Hanneman, 1998a). Birhman & Hosaka (2000) introduced the Sli gene by crossing into cultivated diploid potatoes and confirmed its expression in the genetic background of cultivated diploid potatoes. This facilitates to obtain selfed progeny of diploid potatoes, and continuous selfing may produce highly homozygous lines, which are attractive in genetic analyses, genetic fixation of traits, production of TPS (true potato seed) varieties with genetic uniformity, and heterosis breeding of the potato (Birhman & Hosaka, 2000).…”
Section: Introductionmentioning
confidence: 89%
“…Recently, we found a dominant gene, named S-locus inhibitor gene (Sli), which is sporophytically expressed to inhibit a function of Sallele in pollen, and alters self-incompatible plants to self-compatible ones (Hosaka & Hanneman, 1998a). Birhman & Hosaka (2000) introduced the Sli gene by crossing into cultivated diploid potatoes and confirmed its expression in the genetic background of cultivated diploid potatoes. This facilitates to obtain selfed progeny of diploid potatoes, and continuous selfing may produce highly homozygous lines, which are attractive in genetic analyses, genetic fixation of traits, production of TPS (true potato seed) varieties with genetic uniformity, and heterosis breeding of the potato (Birhman & Hosaka, 2000).…”
Section: Introductionmentioning
confidence: 89%
“…These characteristics have led to potato being a valuable cash crop for millions of farmers. However, in contrast to diploid wild species of potato (Birhman and Hosaka, 2000), most of the current potato cultivars are autotetraploid and encounter indreeding depression because of narrow genetic background, resulting in disease susceptibility (Bryan and Hein, 2008).…”
mentioning
confidence: 99%
“…The transition from self-incompatible to self-compatible in diploid potato can be done by the introgression of the S-locus inhibitor ( Sli ) gene (Hosaka and Hanneman 1998a, b). By repeated selfings of self-compatible diploid potatoes, more homozygous lines can be obtained (Birhman and Hosaka 2000; Phumichai et al 2005). These authors showed that the level of heterozygosity was decreasing and that no chromosomal regions could be identified that were exclusively heterozygous.…”
Section: Discussionmentioning
confidence: 99%